Limiting therapeutic efforts (LTE) in the intensive care units (ICU). Ethical criteria and decision making processes - Luis Evelio Aristizábal Franco (Revista Colombiana de Bioética, 2015)
This research explains the nature of ethical dilmmas in respect to the decisions of therapeutic limitations, its bioethical, legal, and jurisprudential scopes in the intensive care units in the metropolitan area of Pereira, considering the health team, patient family, and the applicability of the Colombian rules in the actions of judges and prosecutors. It was done through triangulation of social investigation techniques; qualitatively grounded theory was utilized; quantitatively a survey was applied, analyzed subsequently through descriptive and inferential statistics. Described are the types of tension between actors and ethical dilemmas in such cir-cumstances, resolution of the mentioned components, and their interaction in decision making. It shows that in ethical and legal decision making there exists some contradiction and stresses the importance of bioethics and its presence in hospital ethical committees in order to seek resolution to ethical dilemmas that should not be based solely on monodisciplinary responses by the doctors. It stresses the need for the actions of lawyers to be enriched with discourse and pluralistic and multidisciplinary analysis.